Cenomanian vertebrates from Algora (central Spain): New data on the establishment of the European Upper Cretaceous continental faunas. (November 2020) - Pérez-García, A.; Bardet, N.; Fregenal-Martínez, M.A.; Martín-Jiménez, M.; Mocho, P.; Narváez, I.; Torices, A.; Vullo, R.; Ortega, F.
Abstract: The palaeontological area of Algora (Guadalajara Province, central Spain) provides the largest concentration of vertebrate macroremains for the Cenomanian of south-western Europe. The available faunal list for Algora, based on the analysis of scarce remains collected in geological surveys carried out more than thirty years ago, was never updated. Therefore, and despite the great potential of this site to reveal novel information about the composition of the vertebrate fauna from the base of the Upper Cretaceous in the continent, the previous determination of many of the taxa recognized there is identified here as inaccurate or erroneous (e.g., the identification of two actinopterygian fishes, a single crocodyliform, the helochelydrid turtle Helochelys danubina and carcharodontosaurid dinosaurs). Recent fieldwork campaigns have provided numerous remains, including those of clades poorly represented so far, as well as others hitherto unknown at this site. The new faunal list proposed here included the lepisosteoid Obaichthys africanus, the helochelydrid aff. Plastremys lata, the pleurodiran Algorachelus peregrina, an indeterminate elasmosaurid, a non-eusuchian neosuchian and a eusuchian crocodyliform, a likely abelisaurid theropod and a lithostrotian sauropod. The study of these taxa provides new information about the palaeobiogeography and temporal distributions of some lineages, and increases knowledge about the poorly-known transition between the Lower and the Upper Cretaceous faunas in Europe. This faunal replacement, in which several well-represented lineages in the uppermost Cretaceous were established, is recognized as strongly conditioned by climate changes that took place between the end of the Early Cretaceous and the beginning of the Late Cretaceous. Highlights: The largest European Cenomanian concentration of macrovertebrates comes from Algora. Recent fieldwork campaigns in Algora have provided numerous remains. The faunal list of the site is updated here. Information about the Early to Late Cretaceous faunal transition is provided. This replacement is recognized as strongly conditioned by climate changes.